2022
DOI: 10.3389/fendo.2022.890029
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Dehydroepiandrosterone and Dehydroepiandrosterone Sulfate Are Associated With Coronary Heart Disease in Men With Type 2 Diabetes Mellitus

Abstract: AimsSex hormones play an important role in the pathogenesis of cardiovascular disease (CVD). This cross-sectional study aimed to explore the associations of dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS) with coronary heart disease (CHD) and stroke in middle-aged and elderly patients with type 2 diabetes mellitus (T2DM).Materials and MethodsA total of 995 patients with T2DM were included in the study analysis. Serum levels of DHEA and DHEAS were quantified using liquid chromatography–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…Moreover, low DHEA levels correlated with cardiovascular disease, including coronary heart disease, myocardial infarction, and stroke, in participants with type 2 diabetes mellitus from 10 communities in Shanghai, China 9 . Similarly, our previous study identified a relationship between low DHEA levels and coronary heart disease in men with type 2 diabetes mellitus 15 . Conversely, a significant relationship was not identified between DHEA and the incidence of cardiovascular disease in studies of women in the general population or those with type 2 diabetes mellitus 9,15,23 .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, low DHEA levels correlated with cardiovascular disease, including coronary heart disease, myocardial infarction, and stroke, in participants with type 2 diabetes mellitus from 10 communities in Shanghai, China 9 . Similarly, our previous study identified a relationship between low DHEA levels and coronary heart disease in men with type 2 diabetes mellitus 15 . Conversely, a significant relationship was not identified between DHEA and the incidence of cardiovascular disease in studies of women in the general population or those with type 2 diabetes mellitus 9,15,23 .…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, our previous study identified a relationship between low DHEA levels and coronary heart disease in men with type 2 diabetes mellitus 15 . Conversely, a significant relationship was not identified between DHEA and the incidence of cardiovascular disease in studies of women in the general population or those with type 2 diabetes mellitus 9,15,23 . Sex‐specific differences regarding these associations remain unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the conclusions drawn from the MR analysis were in accordance with the findings of several epidemiological studies. Lower levels of DHEAS were associated with a higher incidence of cardiovascular disease and cardiovascular disease-related mortality in males and females ( 35 38 ) which might result from low DHEAS-associated hyperlipidemia. However, the exact mechanism underlying this regulatory effect remains unclear and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it may reflect ACTH deficiency and has been studied as a potential additive biomarker to ACTH 1-24 stimulation in the diagnosis of adrenal insufficiency ( 24 , 25 ). However, DHEAS levels decrease with age ( 26 ) and with chronic diseases such as diabetes mellitus ( 27 ), autoimmune disease ( 28 ), and cancer ( 29 ), and the lack of OAI-specific, age-specific reference ranges all may limit its use. Nevertheless, as access to an endocrinologist and ACTH 1-24 stimulation testing may not be readily available to all clinicians, the combination of low/low-normal morning cortisol, DHEAS, and ACTH levels several hours after the last dose of opioids may be used as a preliminary screening tool for OAI.…”
Section: Diagnostic Considerations In Oaimentioning
confidence: 99%